PROSPECTS FOR THE USE OF THE RESOURCE BASE ZAVALLYA GRAPHITE DEPOSITS - Lyzhachenko, N.; Nikolaevskyj, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Zavallya deposit exploited at this stage as a complex object. Traditionally the field developed graphite ore. Аs related components used only charnockites and quartzites, stored garnet ore. Other related components studied not enough. These clays and loams, sands, mineral paint, graphite ore beneficiation products, jasper, that came on the field expanded greatly. It is necessary to hold them to study for selective extraction in the further development field.